The Role of Adaptive Leadership in Times of Crisis: A Systematic Review and Conceptual Framework - Michele Kremer Sott; Mariluza Sott Bender (Merits)
Leading multidisciplinary teams requires not only strong leadership skills, but also a supportive organizational environment. This study examines the key characteristics necessary for adaptive leadership and identifies the main organizational factors that facilitate its development. A systematic literature review, following the PRISMA-P protocol, was conducted, analyzing 33 studies on the traits of adaptive leaders and relevant organizational factors. Based on these findings, we propose a conceptual framework representing the feedback cycle of the adaptive leadership process within organizations and present three propositions associated with this model. The results indicate that the primary characteristics of adaptive leaders include flexibility, empathy, innovation, and long-term vision. Conversely, organizations possess factors that can either facilitate or hinder the development of adaptive leadership, such as organizational culture, structure, innovation history, and strategy. The findings emphasize that orchestrating adaptive teams during times of crisis is especially challenging, requiring additional competencies in resilience and adaptability. This study contributes to the literature by identifying the essential capabilities of adaptive leaders and discussing key considerations for leaders and practitioners seeking to transition from traditional to adaptive leadership.